Phylogenetic relationships and biogeographic range evolution in cat-eyed snakes, Boiga (Serpentes: Colubridae). Issue 1 (15th August 2020) - Weinell, Jeffrey L; Barley, Anthony J; Siler, Cameron D; Orlov, Nikolai L; Ananjeva, Natalia B; Oaks, Jamie R; Burbrink, Frank T; Brown, Rafe M
Abstract: The genus Boiga includes 35, primarily arboreal snake species distributed from the Middle East to Australia and many islands in the western Pacific, with particularly high species diversity in South-East Asia. Despite including the iconic mangrove snakes ( Boiga dendrophila complex) and the brown tree snake ( Boiga irregularis ; infamous for avian extinctions on small islands of the Pacific), species-level phylogenetic relationships and the biogeographic history of this ecologically and morphologically distinct clade are poorly understood. In this study, we sequenced mitochondrial and nuclear DNA for 24 Boiga species and used these data to estimate a robust phylogenetic inference, in order to (1) test the hypothesis that Boiga is monophyletic, (2) evaluate the validity of current species-level taxonomy and (3) examine whether geographic range evolution in Boiga is consistent with expectations concerning dispersal and colonization of vertebrates between continents and islands. Our results support the prevailing view that most dispersal events are downstream – from continents to oceanic islands – but we also identify a role for upstream dispersal from oceanic islands to continents. Additionally, the novel phylogeny of Boiga presented here is informative for updating species-level taxonomy within the genus.